The Application of Electronic Information Technology in Building Engineering - Liu, Shuangshuang; Li, Ping (Journal of Theory and Practice of Engineering Science, 2023)
At the present stage, the degree of social information intelligence continues to increase, electronic information technology has been widely used in various industries, has become an important part of People's Daily life. Electronic information technology can also promote the development and progress of enterprises, most of the enterprises have begun to use electronic information technology in the process of development, it can be seen that the electronic information technology has considerable prospects for development, this paper analyzes the construction engineering enterprises for the use of electronic information technology, hoping to provide a certain reference to the relevant personnel. The paper firstly reviewed the classic newsvendor model and expounded the establishment and solution to the model. Then the model of the supply chain system was established based on the classical newspaper model. Finally, based on the basic theory of repurchase contract, a repurchase agreement was established. The supply chain buyback contract under the newsvendor model can not only realize the coordination of supply chain, but also realize the distribution of profit in the supply chain.